2018
DOI: 10.1051/matecconf/201815603006
|View full text |Cite
|
Sign up to set email alerts
|

Study of Acid Hydrolysis on Organic Waste: Understanding The Effect of Delignification and Particle Size

Abstract: Abstract. Organic wastes from Swiettenia marcophylla L, Artocarpus heterophyllus L, Mangifera indica L, and Annona muricata L were prepared by grinding into 0.1875, 0.3750, 0.7500 mm of particle size and delignified by 2% NaOH at 80 o C for 90 minutes. Acid dilution hydrolysis process with H2SO4 1% was performed at 150 o C for 120 minutes in a closed reactor. The effect of particle size and delignification on and reducing sugar concentration were investigated. The result showed (1) leaves that can be used as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This result is in line with other studies. Anwar [18] studied lignin extraction from rice husks using AHP. The result showed that the optimum conditions for lignin isolation were a solvent/solid ratio of 9:1 ml/gr, hydrogen peroxide concentration of 1.5%v, and pH of the mixture of 11.…”
Section: The Effect Of Phmentioning
confidence: 99%
“…This result is in line with other studies. Anwar [18] studied lignin extraction from rice husks using AHP. The result showed that the optimum conditions for lignin isolation were a solvent/solid ratio of 9:1 ml/gr, hydrogen peroxide concentration of 1.5%v, and pH of the mixture of 11.…”
Section: The Effect Of Phmentioning
confidence: 99%